If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = 9 + -8h Add '-9' to each side of the equation. 9 + -9 = 9 + -9 + -8h Combine like terms: 9 + -9 = 0 0 = 9 + -9 + -8h Combine like terms: 9 + -9 = 0 0 = 0 + -8h 0 = -8h Solving 0 = -8h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '8h' to each side of the equation. 0 + 8h = -8h + 8h Remove the zero: 8h = -8h + 8h Combine like terms: -8h + 8h = 0 8h = 0 Divide each side by '8'. h = 0 Simplifying h = 0
| 5x-1y=15 | | 48+4y-18=14y-12-4y | | X+24=32X | | 3a^2+9a+12=0 | | 4k+8-6k= | | x+x=6+2 | | r(r+3)=0 | | 2y=82 | | 3a^2+9a-12=0 | | 1963-5x=1863 | | n+6/21=4/7 | | 3x+1(-2x+9)=7 | | 36-2(6-2x)=-16 | | n+15=3l | | n/11=40/55 | | 4(20x+15)=1180 | | 4t+7-1=19 | | 8(-9)-(-17)= | | -5=x-2 | | .07*(6000-x)=360 | | 9+4x-2=-15 | | X-1-31=4 | | 3(2x+5)-6(x+2)= | | -2m+13=2-3 | | 15+7(2-4x)=-35 | | 4x+14=60 | | .07*(10000-x)=900 | | r=1979+-40x | | 7+4x=3(2+x) | | 2(6+8*7)6(7+9-9)=9 | | 54=3t | | 3a-5=da |